2017
DOI: 10.3847/1538-4357/aa5b99
|View full text |Cite
|
Sign up to set email alerts
|

Candidate X-Ray-emitting OB Stars in MYStIX Massive Star-forming Regions

Abstract: Massive, O and early B-type (OB) stars remain incompletely catalogued in the nearby Galaxy due to high extinction, bright visible and infrared nebular emission in H II regions, and high field star contamination. These difficulties are alleviated by restricting the search to stars with X-ray emission. Using the X-ray point sources from the Massive Young star-forming complex Study in Infrared and X-rays (MYStIX) survey of OB-dominated regions, we identify 98 MYStIX candidate OB (MOBc) stars by fitting their 1-8 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 113 publications
4
33
0
Order By: Relevance
“…In addition, we confirm spectroscopically the B-type status for four OB stars candidates which we have in common (stars 140, 120, 225, and 527 listed in their Table 7). We also confirm spectroscopically eight of the OB candidates listed by Povich et al (2017): their stars 5 and 8 of NGC 6334 and 2,3,17,18,19, and 22 of NGC 6357. Just as reported by Antokhin et al (2008) we also find an X-ray power demarcation between B and O stars corresponding to L bol ∼ 1.4 × 10 38 erg/s.…”
Section: X-ray Counterpartsupporting
confidence: 68%
“…In addition, we confirm spectroscopically the B-type status for four OB stars candidates which we have in common (stars 140, 120, 225, and 527 listed in their Table 7). We also confirm spectroscopically eight of the OB candidates listed by Povich et al (2017): their stars 5 and 8 of NGC 6334 and 2,3,17,18,19, and 22 of NGC 6357. Just as reported by Antokhin et al (2008) we also find an X-ray power demarcation between B and O stars corresponding to L bol ∼ 1.4 × 10 38 erg/s.…”
Section: X-ray Counterpartsupporting
confidence: 68%
“…It stands out as one of the brightest regions in the southern sky at radio wavelengths (Wilson et al 1970), and is one of the few regions within 2 kpc, along with the Orion Nebula Cluster (ONC), to contain over 2000 young stars identified at infrared wavelengths and in X-rays, although it is more embedded and younger (∼1 Myr) than the ONC (Wolk et al 2006(Wolk et al , 2008Winston et al 2011). These studies have identified around 30 OB star candidates, some of which have been confirmed (DeRose et al 2009;Povich et al 2017). At infrared wavelengths the region is dominated by two sources, the mid-infrared bright RCW 38 IRS1 and the near-infrared bright RCW 38 IRS2 (Figure 4; Furniss et al 1975;Frogel & Persson 1974;Smith et al 1999).…”
Section: Introductionmentioning
confidence: 91%
“…We also use class 0/I YSOs (from Povich et al 2017) to probe the star formation activity of filaments where the starless MDCs are. Indeed, Rivilla et al ( , 2014 show that YSOs and low mass pre-main sequence stars tend to be clustered at the massive star-forming sites.…”
Section: Relation Between Mdcs and Filamentsmentioning
confidence: 99%
“…Such statistical lifetime is estimated from the relative number of a given MDC phase to the OB stars. For NGC 6357 we estimate a total number of 60 O-B3 stars from Russeil et al (2012Russeil et al ( , 2017 and Povich et al (2017). We assume a median age of the O-B3 stars to be 1 × 10 6 yr according to Fang et al (2012) and Getman et al (2014).…”
Section: Ngc 6357 and Ngc 6334 Historymentioning
confidence: 99%
See 1 more Smart Citation